Correcting facial asymmetry through guided plate assisted mandibular angle osteotomy - Han, Wenqing; Yichi, Zhang; Kim, Byeong Seop; Sun, Mengzhe; Chai, Gang (Frontiers in Surgery, 2024)
BACKGROUND Asian women prefer a smooth and narrowed mandibular appearance. The purpose of the retrospective cohort study is to evaluate guide plate-assisted mandibular angle ostectomy (MAO) in improving mandiblular symmetry for Asian female patients with mandibular angle hypertrophy (MAH) with normal occlusal relationship.We retrospectively examined 11 patients with asymmetry MAH with normal occlusal relationship who received MAO at Shanghai Ninth People's Hospital between September, 2020, and January, 2022. Preoperative plans were designed based on CT data and executed using metal guide plate during the operation. Preoperative and one-week postoperative CT scans were used to assess measurements including Height_Go, Divergence_Go, ∠ZyZy-GoGo, and osteotomy volume, to evaluate symmetry. For precision, compare the postoperative CT with the preoperative design, assessing osteotomy distance, angle, and volume error. Patient satisfaication was evaluated with Likert Scale in 6-month follow-up. Secondary lipofilling procedures were given as appropriate. Statistical analysis was performed using paired t-tests in SPSS.The mean age of the 11 patients was 28.5 years (range 23-34 years). 2 of these underwent lipofilling procedures. No complications were observed during the following-up.Postoperative results were not statistically different from the design , demonstrating a precision of within 2mm. Height_Go disparity within 5mm get corrected notablly, reducing asymmetry from 15.09% preoperatively to 2.74% postoperatively. Patients satisfaction was rated at 4.5 out of 5 in 6 month follow-up.Conclusions Guide plate-assisted mandibular angle osteotomies achieve effective and precise surgery. This approach demonstrates a safe option for correction for mandibular asymmetry, achieving patient satisfaction.